Relationship Between Pain and Sedentary Behavior in Rheumatoid Arthritis Patients: A Cross‐Sectional Study. Issue 7 (28th June 2021) - O'Leary, Helen; Larkin, Louise; Murphy, Gráinne M.; Quinn, Karen
Abstract : Objective: Despite the known benefits of physical activity, high numbers of individuals with rheumatoid arthritis (RA) remain physically inactive and sedentary. Little is known about the determinants of sedentary behavior (SB) in RA. This cross‐sectional study was undertaken to examine a range of pain characteristics and RA‐related symptoms and their relationship with objectively measured SB. Methods: In total, 76 adults with RA wore an activPAL4 accelerometer (PAL Technologies) over a 7‐day period. Pain characteristics (pain intensity, painful joint count, nonarticular pain), fatigue, sleep, depression, anxiety, and disease activity were assessed. Analyses were first conducted to evaluate correlations with sedentary time. The independent contribution of pain characteristics to variation in SB was analyzed with multivariable linear regression (adjusted for demographic data and disease activity). Results: Participants with valid accelerometer data (n = 72) spent a mean ± SD of 533.7 ± 100.1 minutes/day in SB. Positive associations with daily SB were found for pain intensity (r = 0.31, P < 0.01) and number of painful joints (r = 0.24, P < 0.05) but not nonarticular pain. In multivariable analyses, pain characteristics were not independently associated with SB. Analyses indicated that disease activity had an indirect association with SB mediated by pain intensity. Other correlates of daily SB included anxiety and depression but not fatigue or sleep. Conclusion: Results suggest that while pain and other RA‐related factors do play a role in SB, they do not appear to have a significant influence after accounting for other variables. Future research should investigate SB and the role of factors unrelated to the symptoms of RA.